Social Media As a Platform for Informal Digital Learning of English (IDLE) : A Mixed-Methods Study on Computer Science Students - Susanti Susanti (Universitas Negeri Medan, 2026)
This study explores the affects of social media as a platform for acquiring English from the perspective of Informal Digital Learning of English (IDLE). This study uses mixed-method designs with quantitative and qualitative approaches to the second semesters leaners of STMIK Pontianak, System Information program, consisted of 30 learners the academic year of 2024/2025.With the widespread and extensive use of platforms such as Instagram, Tiktok, YouTube, and other learning applications, learners are increasingly directed to real English content and real-time communication with vary people. This paper learns how social media influences to the development of language skills, including vocabulary, listening, speaking, and intercultural competence. It also investigates learners’ behaviors, motivations, and strategies when engaging with English content online. The results indicate that social media can enrich language acquisition by delivering valuable experience, growing motivation, and helping autonomous learning. However, weaknesses such as inconsistent language input, limited corrective feedback, and potential distractions are also undeniable. In general this study highlights the significance of IDLE in modern language learning and reminds that social media can serve as an effective extra tool for enhancing English proficiency in an engaging way.